PERAN IBU 01 DALAM PENATAAN SETING PRIVASI RUMAH TINGGALNYA (Studi Kasus:Rumah Tinggal lbu-Ibu Anggota Majlis Taklim SALlMAH Yogyakarta) - Sativa Sativa (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2007)
AbstractPeople need interaction control mechanism in their activities,wherever and whenever they do. This mechanism which is named asprivacy, is different among individual or community, depend on theirbackground. This study aims to analyze role of mother with Islamicbackground, in privacy setting arrangement in their houses. Due to oftime limitation, this study is focused on territorial arrangement, as a wayto reach an optimal privacy.This research uses naturalistic qualitative method that Jakesresult from induction of discovered themes. The sampLe of this researchare private houses of member of Persaudaraan Muslimah organizationin Yogyakart2.Themes as results of this study are: occupants and theiractivities, area of house, variety of rooms, roOm activities, accessibilitysequence to the room, main and side entrance, and role of house settingarrangement. Further, the conclusion is: 1) Mother role in territorialarrangement to· reach optimal privacy in her house is very significant.The role in initiating and implementing territorial arrangement especiallyrefer to defense mother privacy (aural) 2) Those territorial arrangementare formed as : arrangement of accessibility sequence of rooms,character and form of border among the rooms. Those territoriality canbe deviced into 4 classifications, as public space, semi public space,semi private space and private space. In special condition thoseterritorial space can be changed depend on activity and user need.Keywords: privacy, territorial arrangement. mother role